Erratum: ZHANG, F. & LIU, X-W. (2009) A review of the subgenus Diestrammena (Gymnaeta) from China (Orthoptera: Rhaphidophoridae Aemodogryllinae). Zootaxa, 2272, 21–36. - Zhang, F.; Liu, X. W. (Zootaxa, 2009)
(Erratum)